2006
DOI: 10.1021/tx060013b
|View full text |Cite
|
Sign up to set email alerts
|

Ester Hydrolysis and Nitrosative Deamination of Novocaine in Aqueous Solutions

Abstract: In aqueous solutions, the kinetic features of both the hydrolysis reaction of the ester function of novocaine in alkaline medium and the nitrosation reaction of the primary amine group of novocaine in mild acid medium were investigated by UV/vis spectroscopy. The ester hydrolysis shows first-order kinetics with respect to both the drug and the nucleophile, OH-, concentrations, thus following a typical S(N)2 (Ac) mechanism. The rate of the reaction decreases strongly with the polarity of the reaction media, ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Procaine or novocaine has been used as a local anesthetic for a long time. The dissociation equilibria of this substance are important to understand its behavior; therefore, it has been considered of interest to study the variation of its acid−base equilibrium constants with salt concentration in different ionic media at 25 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Procaine or novocaine has been used as a local anesthetic for a long time. The dissociation equilibria of this substance are important to understand its behavior; therefore, it has been considered of interest to study the variation of its acid−base equilibrium constants with salt concentration in different ionic media at 25 °C.…”
Section: Introductionmentioning
confidence: 99%
“…74 The rate of alkaline hydrolysis of the local anaesthetic novocaine (diethylaminomethyl 4-aminobenzoate) was reported. 75 Kinetic studies of the reactions of polyalkylamines with aryl acetates and aryl methyl carbonates at pH 7-11.5 showed that concerted mechanisms operate. 76 The hydrolysis of glycine methyl ester, CH 2 (NH 2 )CO 2 Me, and methionine methyl ester, MeSCH 2 CH 2 CH(NH 2 )CO 2 Me, was catalysed with high effectiveness by the Cu(II) complex of N ,N ,N ,N -tetramethylethylenediamine, the observed catalytic enhancement being 10 4 -fold.…”
Section: (A) Carboxylic Acids and Their Derivatives (I) Esters Lactomentioning
confidence: 99%
“…As an example, in the case of TCA the input values of A a ¼ 0.025-the absorbance reading at the lowest pH-and A b ¼ 0.924-the absorbance reading at the highest pH-gave the optimized pK a1 ¼ 2.27 AE 0.02 reported in Table 1, along with the pK a1 measured for the other anaesthetics. 18 (See Fig. S1 of ESIw.…”
Section: Absorption Spectramentioning
confidence: 99%